Mediation and learning of Philosophy at the University: A pedagogical experience with meaning in dark times for humanities - Fallas-Vargas, Fabrizio (2021)
Thinking and rethinking higher education pedagogy, so that is truly meaningful, requires great consideration of what pedagogical mediation is in terms of higher education, which is no different from what is actually done for all the other educational domains and levels. This is especially the case when learning is prioritized over teaching and when mediation is regarded as: the handling of content, form and learning   in order for students to take over the learning experience. This paper aims to share a particular learning experience in a philosophy class held at a public university in Costa Rica. Experiences were collected and systematized that one may ponder on the actions, and the narrative is generated to serve as a basis for establishing some of the most meaningful findings so they can be translated into key elements for a university pedagogy with a meaning. In order to attain the aforementioned aim, this remarkable learning experience has been described and systematized founding the basis of this account.